The Network Capital of the Cossack Youth as an Element of the Social Capital of the Russian Cossacks - A. S. Shilyaeva; S. V. Kurapov; M. E. Zabolotnikov; S. V. Petrova (Дискурс, 2022)
Introduction. The article considers the modern Russian Cossacks as a complex social object in the trinity of interpersonal, intragroup and intrapersonal communications. The ethno markers of the Cossacks that influence the perception of “friend or foe” are determined; the problem of the concept of the network capital of the Cossacks is formulated.Methodology and sources. The section formulates the construction of network capital from the point of view of structuring social relations in the network approach, and from the point of view of the culture of interactive communication in the network space. The main approaches to the definition and measurement of network capital are shown, its specificity for the social group of Cossack youth is revealed. The network model of the Cossacks and Cossack youth is described as a whole and its part. The role of state-forming values in the Cossack environment is shown. The largest network Cossack youth organizations from different regions of Russia are presented.Results and discussion. The article describes the methodology for researching network capital, organized at the All-Russian Gathering of Cossack Youth in the fall of 2021 in the city of Krasnoyarsk. On the basis of four groups of values of the Cossack youth, namely social, personal, values of the Cossacks and values of the direct contact environment, a network analysis of positive and negative relationships, as well as relationships in subgroups of values, is carried out. As a comparative analysis, the results of measuring the network capital of students of the IT faculty of the evening department are used, which show a clear professional orientation and belonging to a generalized supranational community of IT specialists and a low team-building potential. The authors conclude that the construction of “network capital” is more often used in an empirical sense to obtain information about the mechanisms of access to resources or some kind of influence through network relations.Conclusion. In general, the theory of “network capital” is in the process of its formation and requires further scientific understanding. In the ongoing process of institutionalization of the Cossacks, contradictions often arise between the traditions and values of modern society, which the Cossack youth seeks to resolve in a compromise way. It is concluded that the network capital of the Cossack youth is in the stage of its active accumulation and continuous transformations.